Growth and Productivity Assessment of Short-Duration Rice (Oryza sativa L. and Upland NERICA) Genotypes in Semiarid North-Central Namibia - Simon K. Awala; Kudakwashe Hove; Vistorina Shivute; Johanna S. Valombola; Pamwenafye I. Nanhapo; Yoshihiro Hirooka; Osmund D. Mwandemele; Morio Iijima (Advances in Agriculture)
In semiarid regions, drought is the major threat to crop production, but climate change and variability often bring floods to the regions, forming seasonal wetlands causing damage to local, drought-adapted staple grains and, hence, low yields and food deficit. Introduction of the semiaquatic crop rice (Oryza spp.) to these semiarid wetlands could complement the dryland crop low yields and overcome the food shortage problem. A field experiment was carried out at the University of Namibia-Ogongo Campus during the 2016/2017 and 2017/2018 cropping seasons to assess the growth and yield of rice genotypes. Twelve short-duration rice genotypes, nine from the International Rice Research Institute (IRRI) and three locally grown upland NERICA genotypes, were used. Parametric analysis of variance was performed to test their effects on crop growth and yield characters. The results showed significant genotype by year interaction for days to heading, plant height, the number of tillers per m2, shoot biomass, the number of panicles per m2, 1000-grain weight, harvest index, and grain yield. The IRRI genotypes produced a higher number of tillers, shoot biomass, and grain yield than the NERICA ones, which were early maturing, were taller, and had higher 1000-grain weight across the years. Generally, most of the genotypes had lower grain yield and higher shoot biomass in the first year, due to the prevailing cool, rainy, and seemingly cloudy weather conditions associated with lower temperature and lower solar radiation. Grain yield was positively correlated with most characters but negatively correlated with the 1000-grain weight. These results demonstrate the yield superiority of IRRI genotypes over their early-maturing NERICA counterparts. However, further studies on morphological characters and drought tolerance of the IRRI genotypes are warranted to ascertain production sustainability under semiarid environments.